Durability of Composites in a Marine Environment 2 (Solid Mechanics and Its Applications,, 2018)
This book presents selected papers from the 2nd Workshop on "Durability of Composites in a Marine Environment", which was held in Brest, France in August 2016. Providing an overview of the state of the art in predicting the long-term durability of composite marine structures, it addresses modelling water diffusion; damage induced by water accelerated testing, including durability in design; in-service experiences; ocean energy; and offshore applications. Ensuring long-term durability is not only necessary for safety reasons, but also determines the economic viability of future marine structures, and as such, the book is essential reading for all those involved with composites in the marine industry, from initial design and calculation through to manufacture and service exploitation. It also provides information unavailable elsewhere on the mechanisms involved in degradation and how to take account of them. .